2012
DOI: 10.1185/03007995.2012.665362
|View full text |Cite
|
Sign up to set email alerts
|

Practical guidelines on the use of paliperidone palmitate in schizophrenia

Abstract: Paliperidone palmitate offers some advantages in terms of tolerability, simplicity of treatment initiation and long duration between injections. The consensus of the authors is that rather than reserving paliperidone palmitate for use in difficult-to-treat or refractory patients, it could be used to promote adherence and prevent relapse earlier in the course of the illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“… 19 Nevertheless, some recent studies have been identified. Results from previous observational studies 9 , 10 indicate that RLAI is associated with lower hospitalization rates compared to oral antipsychotics. A Hungarian registry-based observational follow-up study including 9,567 schizophrenic patients 10 also reported longer time to treatment discontinuations with RLAI than with oral antipsychotics.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“… 19 Nevertheless, some recent studies have been identified. Results from previous observational studies 9 , 10 indicate that RLAI is associated with lower hospitalization rates compared to oral antipsychotics. A Hungarian registry-based observational follow-up study including 9,567 schizophrenic patients 10 also reported longer time to treatment discontinuations with RLAI than with oral antipsychotics.…”
Section: Discussionmentioning
confidence: 88%
“…This is very comparable to the Cohort for the General study of Schizophrenia, which included more than 1,500 patients (mean age, 38 years; 68% of male). 10 …”
Section: Discussionmentioning
confidence: 99%
“… 28 Most often, they have been reserved as a “last resort” for use in patients who have severely deteriorated or frequently relapsed, and only after the failure of orally administered pharmacotherapies. 22 , 29 Paliperidone palmitate (PP), is a once-monthly LAI atypical antipsychotic, approved in the US, Europe, and all major Asia-Pacific countries for acute and maintenance treatment of schizophrenia. Compelling evidence supports PP’s effectiveness and safety 1 , 17 , 30 40 – including in Asian patients with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike most other long‐acting preparations for injection, paliperidone palmitate does not require oral supplementation . The pharmacokinetic properties of paliperidone palmitate allow for the rapid attainment of a therapeutic serum concentration within 24 hours, and the drug's sustained release characteristics allow for monthly administration .…”
Section: Introductionmentioning
confidence: 96%